A Framework for Small Satellite Architecture Design. Issue 1 (13th September 2016) - Qaisar, Sana U.; Ryan, Michael J.; Tuttle, Sean L.
Abstract: The availability of miniaturized, commercial‐off‐the‐shelf (COTS), low‐cost satellite components has encouraged the design and development of "small" satellites by relatively inexperienced organizations and individuals seeking low‐cost and fast‐delivery missions with "good enough" reliability requirements, through non‐traditional risk‐taking approaches. Currently, there are no standards or guidelines for optimal architecting of such plug‐and‐play satellites. Consequently, the accepted trade‐off, between the available limited resources and the reliability compromise, in the architectural design space, is likely to be sub‐optimal, resulting in a sub‐optimized capability. In this paper, we propose a systematic framework for informed and optimal decision making which allows the designer to dynamically explore a multitude of solutions derived from relevant COTS databases, to determine an architecture that optimizes the system reliability under the given constraints. The proposed framework is demonstrated through the presentation of a commercial Cube‐Satellite example based on real data. This work can potentially contribute to small satellite standardization efforts.